Maize yield reduction and economic losses caused by ground-level ozone pollution with exposure- and flux-response relationships in the North China Plain. (15th December 2022) - Wang, Tuanhui; Wang, Feng; Song, Hongquan; Zhou, Shenghui; Ru, Xutong; Zhang, Haopeng
Abstract: Ground-level ozone (O3 ) has negative effects on agricultural crops. Maize is an important grain crop in China. The North China Plain (NCP) serves as the major crops' production area of China and experiences severe ozone pollution. Using the ground-level ozone simulated by an atmospheric chemistry transport model (WRF-Chem), we quantified the yield reduction and economic losses of maize during 2015–2018 over NCP based on exposure-response AOT40 (accumulation of hourly O3 concentration exceed 40 ppb) and flux-response POD6 (phytotoxic dose of ozone over 6 nmol m −2 s −1 ). Results showed that the ozone concentration, AOT40, and POD6 clearly increased from 2015 to 2018 in growing season of maize over NCP. The four-year annual mean ozone concentration, AOT40, and POD6 were 0.055 ppm, 18.02 ppm h, and 5.02 mmol m −2, respectively. At county level, the relative loss of maize yield (MRYL) based on AOT40 and POD6 had clearly spatio-temporal differences in NCP. The average MRYLs of AOT40 and of POD6 from 2015 to 2018 were 10.4% and 21.4%, respectively, and these reductions were associated with 2399 million and 5637 million US dollars, respectively. This study suggests that surface ozone increased the yield losses of maize, and indicates that further reductions in ozone concentrations can enhance the food security in China. Highlights: Compare exposure-response with flux-response ozone metrics of maize over NCP. The first flux-response evaluation of the effect of ozone on maize production in China. Annual mean relative yield loss estimated by AOT40 and POD6 were 10.4% and 21.4%, respectively.